2005
DOI: 10.1021/jf051202n
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Headspace Analysis of the Release of Volatile Organic Compounds from Ethanolic Systems by Direct APCI-MS

Abstract: Static equilibrium headspace was diluted with a stream of nitrogen to study the stability of the volatile headspace concentration. The headspace dilution profile of 18 volatile compounds above aqueous and ethanolic solutions was measured in real time using atmospheric pressure chemical ionization-mass spectrometry. Under dynamic conditions the volatiles headspace concentration above water solutions decreased readily upon dilution. The presence of ethanol helped to maintain the volatile headspace concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 18 publications
7
62
0
Order By: Relevance
“…Most of the other operative conditions were chosen in accordance with a previous work [18] (see Table 3). The number of extraction strokes per extraction cycle for a given sample volume were optimized so that analyte recoveries would fit in the 10-80% target to observe a clear exponential area decrease.…”
Section: Itex Methods Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the other operative conditions were chosen in accordance with a previous work [18] (see Table 3). The number of extraction strokes per extraction cycle for a given sample volume were optimized so that analyte recoveries would fit in the 10-80% target to observe a clear exponential area decrease.…”
Section: Itex Methods Parametersmentioning
confidence: 99%
“…In the first category, the most common approach is headspace solidphase microextraction (SPME) [12,13], although other techniques such as dynamic headspace extraction methods coupled to gas chromatography (GC) have been also applied [14,15]. In the second category we find direct atmospheric-pressure chemical ionization mass spectrometry (APCI-MS) [8,[16][17][18][19] and proton transfer reaction mass spectrometry (PTR-MS) [20][21][22]. Techniques in this last group are in most cases, not sensitive enough for the direct monitoring of aroma compounds present at low levels in the products.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is called the Marangoni effect and it has been proposed to explain the higher release of aroma compounds from ethanolic solutions. [22] In some sparkling drinks, e.g. Champagne and beer, it has been postulated that surface-active substances can accumulate at the bottom of the rising bubble.…”
mentioning
confidence: 99%
“…With this modification in place, the release of aroma from ethanolic solutions was studied using the dynamic headspace dilution technique. This showed that, although ethanol tended to reduce the gas-phase aroma concentration at equilibrium due to a changed partition value, the concentration in the gas phase during dynamic headspace dilution was greater for some compounds than for the corresponding water control (Tsachaki et al, 2005;Tsachaki et al, 2008). This behaviour can be attributed to the Marangoni effect, a sequence of events that starts with ethanol evaporation from the air-liquid interface.…”
Section: Measuring Aroma Release In Ethanolic Beveragesmentioning
confidence: 98%